2008
DOI: 10.1051/agro:2008017
|View full text |Cite
|
Sign up to set email alerts
|

Organic and conventional management of mixtures of wheat and spring cereals

Abstract: -Cereal mixtures may provide both organic and conventional producers with a more sustainable approach in reducing weed pressure, crop rotation flexibility, improved yield stability, buffering against pests and diseases, minimizing soil variability and increasing animal feed value. We examined the response of small grain mixtures containing wheat, oats, barley and triticale to varying degrees of natural competition and environmental stress at three locations in central Alberta, Canada. One modern and one herita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 21 publications
(26 reference statements)
2
36
0
2
Order By: Relevance
“…There is limited documented research work on grain intercropping in the NGP and the results of this research are inconsistent. Overyielding and greater yield stability have been observed in some crop combinations and under some conditions, but not in others (Carr et al 1995(Carr et al , 2004Szumigalski and van Acker 2005;Kaut et al 2008;Pridham and Entz 2008;Hummel et al 2009;Nelson et al 2012).…”
Section: Annual Polyculturementioning
confidence: 96%
“…There is limited documented research work on grain intercropping in the NGP and the results of this research are inconsistent. Overyielding and greater yield stability have been observed in some crop combinations and under some conditions, but not in others (Carr et al 1995(Carr et al , 2004Szumigalski and van Acker 2005;Kaut et al 2008;Pridham and Entz 2008;Hummel et al 2009;Nelson et al 2012).…”
Section: Annual Polyculturementioning
confidence: 96%
“…Research on agronomic aspects of organic farming has shown that crop yields tend to be lower in organic farming Kaut et al, 2008), albeit less variable and less susceptible to drought (Lotter, 2003). Organic farming methods tend to increase soil organic matter and thus enhance soil fertility (Langmeier et al, 2002;Mäder et al, 2002), making it less dependent on external inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Mixtures of Park wheat and Manny barley, for example, were shown to have equal or greater yields than monoculture wheat under organic conditions, which may be partly attributed to the weed suppressive ability of Manny barley [51]. Mixtures of AC Superb and AC Intrepid (1:1 or 1:2) wheat were found to have greater stability than AC Superb alone [53].…”
Section: Weed Managementmentioning
confidence: 97%
“…Crop mixtures have been considered as an agronomic approach to reducing weed pressure, protecting against pests and diseases, and enhancing yield stability [51,52]. Mixtures of Park wheat and Manny barley, for example, were shown to have equal or greater yields than monoculture wheat under organic conditions, which may be partly attributed to the weed suppressive ability of Manny barley [51].…”
Section: Weed Managementmentioning
confidence: 99%